Retrospective analysis of the process of organizing education in the native language - Uzakova Maftuna Abdirazzakovna (THE INNOVATION ECONOMY, 2026)
This article provides a retrospective analysis of the process of organizing native language education. The process of teaching native language has a long history, and it has developed in different periods depending on social, cultural and scientific factors. The study analyzes the historical stages of native language education, the evolution of methodological approaches, and the factors that influenced the formation of educational content. Also, the achieve ments and problems of native language education in different periods are considered and compared with modern approaches. The results of the study are important in developing scientific and methodological recommendations aimed at improving the quality of native language education.